Evaluating treatment and care outcomes for neuromuscular diseases in a pediatric intermediate care setting - Brisca, Giacomo; Strati, Marina F.; Canzoneri, Francesca; Mariani, Marcello; Pirlo, Daniela; Romanengo, Marta; Tardini, Giacomo; Brolatti, Noemi; Buratti, Silvia; Pedemonte, Marina; Fiorillo, Chiara; Striano, Pasquale; et al. (Frontiers in Pediatrics, 2025)
BackgroundNeuromuscular disorders (NMDs) represent a complex group requiring specialized care, often straddling the needs between general pediatric wards and Intensive Care Units (ICUs). Our research focuses on the role of a newly established pediatric Intermediate Care Unit (IMCU) in this context.MethodsWe conducted a single-center retrospective observational study, encompassing patients with NMDs admitted to the newly established pediatric IMCU at IRCCS Istituto Giannina Gaslini, Genoa, Italy, from January 2021 to June 2023. The study assessed demographics, clinical characteristics, therapeutic management, length of stay, and outcomes including mortality 28 days post-discharge.ResultsSixty-three patients (median age 12, female 58.7%) were included. The majority of admissions were due to neurological issues (39.7%) and respiratory complications (22%), with a significant proportion of patients requiring initiation or potentiation of respiratory support (59%). Factors such as the presence of tracheostomy (p = 0.021), the need for antibiotics (p = 0.025), and parenteral nutrition (p = 0.026) were associated with ICU admissions while steroid treatment (p = 0.047) increased IMCU stay.ConclusionsThe establishment of the IMCU has shown promising results in managing NMDs patients, serving as a crucial step-down unit for ICU patients and a step-up unit for those with worsening conditions in low-intensity care units. It has led to decreased ICU admissions and shorter ICU stays, suggesting potential healthcare costs and patient comfort benefits. The study underscores the importance of pediatric IMCUs in providing specialized care for children with NMDs, balancing the need for intensive monitoring and treatment in a less intensive setting than an ICU.